Coconut-growing soils in southern Karnataka: Characterization and classification - Avinash, R.K.; Anil Kumar, K.S.; Karthika, K.S.; Kalaiselvi, B.; Sujatha, K. (Journal of Plantation Crops, 2019)
A study was carried out to characterize and classify major coconut-growing soils of southern Karnataka and to evaluate the suitability of these soils for coconut cultivation. Seven locations were selected on the map of coconut-growing areas in southern Karnataka and delineated based on the variability of agro-climate with the help of land resource map and report of Karnataka state, generated at 2,50,000 scale by ICAR-NBSSLUP. The regions included Hosadurga (central dry zone), Gubbi and Turuvekere (eastern dry zone), Krishnarajapet (southern dry zone), Arasikere (southern transition zone), Belthangadi and Brahmavara (coastal zone) representing the density of coconut-growing areas in different agro-climatic zones. Soil profiles were studied at these selected sites. The coconut growing soils of southern Karnataka are generally deep, gravelly and well drained, sandy clay loam to clayey in texture with good structure. Soils of high rainfall areas of Belthangadi and Brahmavara were strongly acidic and rich in soil organic carbon, whereas other locations of sub-humid to semi-arid were near neutral to moderately alkaline soils with medium organic carbon content. Cation Exchange Capacity and base saturation were very low in coastal red and lateritic coconut soils and ranged from medium to high in other areas. The major taxa of the soils identified at sub-group level of soil taxonomy are Rhodic Kanhaplustults, Ustic Kandihumults, Rhodic Paleustalfs, Typic Rhodustalfs and Vertic Haplustepts.